Functional echocardiographic preload markers in neonatal septic shock. (12th December 2022) - Saini, Shiv Sajan; Sundaram, Venkataseshan; Kumar, Praveen; Rohit, Manoj Kumar
Abstract: Background: There are no established clinical or laboratory markers of preload adequacy and fluid responsiveness in management of neonatal shock. Functional echocardiographic preload markers are evaluated in children and adults, but there is no data in neonatal septic shock. We evaluated five functional echocardiographic preload markers during intravenous volume resuscitation in neonatal septic shock. Objective: (1) To compare baseline functional echocardiographic preload markers between neonates with septic shock and their "matched" healthy controls. (2) To compare echocardiographic preload markers before and after intravenous volume resuscitation. Methods: In this cohort study, we enrolled neonates with septic shock (cases) and recorded five preload markers – inferior vena cava collapsibility index (IVC-CI), left ventricular end-diastolic (LVEDV) & end-systolic volume (LVESV) and their indices (LVEDVI, LVESVI) – before initiation of intravenous fluid resuscitation (baseline evaluation). An equal number of "matched hemodynamically stable" controls were recruited, who underwent functional echocardiographic assessment once. In neonates with shock, we recorded these markers again after volume resuscitation. Results: We analyzed 46 neonates (23 cases and 23 controls). Neonates with shock had significantly elevated baseline IVC-CI as compared to controls [53% (21, 100) vs. 20% (15, 24) respectively, p -value = .01). Rest 4 echocardiographic markers (LVEDV, LVESV, LVEDVI, and LVESVI) were comparable between cases and controls. Sixteen neonates (70% of 23) received intravenous fluid resuscitation and rest 7 (30%) were started directly on vasoactive drugs. None of the preload markers changed significantly after volume resuscitation as compared to the baseline values including IVC-CI, which was almost significant [74% (33, 100) at baseline to 48% (13, 93) after 10 mL/kg and 50% (40, 69) after 20 mL/kg, ( p = .05). All preload markers were comparable between survivors and non-survivors. Conclusion: Neonates with septic shock had significantly elevated IVC-CI at baseline as compared to hemodynamically stable neonates. None of the preload markers changed significantly after volume resuscitation as compared to the baseline values including IVC-CI, which was almost significant.